2014
DOI: 10.1136/bmjopen-2013-004075
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and reinfection afterStaphylococcus aureusbacteraemia in individuals with and without HIV-1 infection: a case–control study

Abstract: ObjectivesIndividuals infected with HIV-1 are at an increased risk of Staphylococcus aureus bacteraemia (SAB). The aim of this study was to investigate mortality rate and risk of reinfection associated with SAB in HIV-1-infected individuals compared to individuals without HIV-1 infection.SettingUniversity hospital treating a third of the estimated 5000 individuals with HIV infection in Denmark.ParticipantsHIV-1-infected (n=82) and sex-matched and age-matched uninfected (n=163) individuals with SAB in the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
(32 reference statements)
0
7
1
Order By: Relevance
“…Although the short-term outcomes of medical patients at Groote Schuur Hospital are generally poor, with only 65% surviving to 12 months post-discharge (Stuart-Clark et al, 2012), this does not fully explain the poor early outcomes observed in this study, where the majority of deaths were possibly SAB-related. Over a fifth of the patients had an HIV co-infection, but this was not associated with mortality or complicated infection, in contrast to other reports (Jaliff et al, 2014). This suggests that specific host-or pathogen-related factors may account for the worse outcomes observed compared to other settings.…”
Section: Discussioncontrasting
confidence: 57%
“…Although the short-term outcomes of medical patients at Groote Schuur Hospital are generally poor, with only 65% surviving to 12 months post-discharge (Stuart-Clark et al, 2012), this does not fully explain the poor early outcomes observed in this study, where the majority of deaths were possibly SAB-related. Over a fifth of the patients had an HIV co-infection, but this was not associated with mortality or complicated infection, in contrast to other reports (Jaliff et al, 2014). This suggests that specific host-or pathogen-related factors may account for the worse outcomes observed compared to other settings.…”
Section: Discussioncontrasting
confidence: 57%
“…Based on local and national databases, we expect a failure to treat and relapse rate of < 5% for patients with uncomplicated SAB alive at day 7 and a 90-day all-cause mortality rate of approximately 7%, corresponding to a recovery rate of 88% [20]. However, available data on recurrence and death in this select group of patients is sparse.…”
Section: Statisticsmentioning
confidence: 99%
“…4042 Injection drug users are at very high risk of repeated BSIs due to S. aureus including methicillin-resistant strains. 4345 Recently, countries with high IDU reported increases in BSI rates. 29,31 HIV patients represent a particularly high risk group for invasive disease with S. pneumoniae , both in developing and developed countries except for Southeast Asia where 47% BSIs are caused by NTS.…”
Section: Hiv/aidsmentioning
confidence: 99%
“…45 Recent evidence suggests that MRSA and CA-MRSA are becoming an emerging epidemic among HIV patients in some developed countries. 43,45 Therefore, depending on the local epidemiology, empirical use of glycopeptides or daptomycin can be considered in those settings. 49 In Africa and Southeast Asia, NTS show high prevalence of multidrug resistance, particularly to antibiotics regarded as first line in low resource settings, that is, ampicillin, chloramphenicol, and co-trimoxazole.…”
Section: Hiv/aidsmentioning
confidence: 99%